2011
DOI: 10.1177/1741826711421301
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity is inversely associated with microalbuminuria in hypertensive patients at high cardiovascular risk: data from I-SEARCH

Abstract: In hypertensive patients at high cardiovascular risk, physical activity is an independent predictor for a decreased risk of microalbuminuria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…MAU is closely related to some CVD risk factors including age, smoking, hypertension, diabetes, dyslipidaemia and lack of physical activity. 25,26 MAU is associated with impaired arterial and venous endothelium-dependent vasodilation in patients with Type 2 DM. 27–29…”
Section: Discussionmentioning
confidence: 97%
“…MAU is closely related to some CVD risk factors including age, smoking, hypertension, diabetes, dyslipidaemia and lack of physical activity. 25,26 MAU is associated with impaired arterial and venous endothelium-dependent vasodilation in patients with Type 2 DM. 27–29…”
Section: Discussionmentioning
confidence: 97%
“…The presence of microalbuminuria is a marker of vascular damage and endothelial dysfunction, so it is the earliest sign of renal disease in many cases [15,20,21]. Microalbuminuria was found to be a predictor of cardiovascular events and worsening renal function [11][12][13][14]. An association between increased albuminuria even in the normal range and increased risk for cardiovascular events has been determined [15,22].…”
Section: Discussionmentioning
confidence: 99%
“…Microalbuminuria is accepted as an independent risk factor for cardiovascular events and worsening renal function [11][12][13][14]. Also it is a marker of endothelial dysfunction [15].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that serum NO levels decreased, and serum ET-1, ICAM-1, VCAM-1, and hsCRP levels significantly increased in the Q 1+2+3 group compared with the Q 4 group that were classified either by MWSS or by PWSS. ACR is not only one of the renal functional markers but is also regarded as one of the most important markers of generalized endothelial dysfunction 24,25 . Endothelial dysfunction leads to impairment of the endothelial barrier, which results in increased transvascular albumin leakage 24,26 .…”
Section: Discussionmentioning
confidence: 99%